A talha religiosa da segunda metade do século xix no Rio de Janeiro, através do seu artista maior, Antonio de Pádua e Castro - Fernandes, Cybele Vidal Neto (1991)
Situate properly, in the historiagraphy of the Art in Brazil, the figure of the artist here in bef'ore mentioned. At the same time, it broaches the wood carving technic problems in that stage of the history, making use of the works of Pádua e Castro, whose production is the most expressive of that period. It was imperative, as first stage of the work, to realize an historical-documental research, which allow us to inventory the whole work of the artist. Realizing the art as an artistic manifestation, arised from the cultural practice, owning a particular way to express the ideas of the artist, accordinly to his time and the society, it was selected specific informations and remade considerations about expressive facts, in order to make it possible a better comprehension of (or bring us near to) the speech of that time. Preliminarly, it was conducted a reflection about the wood carving technic, its role in the religious scenery and its estilistic evolution, in Portugal and Brazil, with the intention to familiarize the reader with. the theme to be dealed with. The description and ichonographic analysis of his work allowed us to identify the formal vocabulary and the stylistict tendencies revealed along his production.